Al-Quran Learning for Autistic Children in School: Pembelajaran Al Quran Terhadap Anak Autis Di Sekolah - Siti Maratus Soleha; Imam Fauji (Academia Open, 2022)
This study aims to find out how the strategy is and how the level of difficulty in learning the Koran for autistic children is at the Labschool Umsida school, Candi Sidoarjo and to find out what are the obstacles and supports in the learning process at the Labschool Umsida school, Candi Sidoarjo. What is the strategy and what is the level of difficulty in learning the Koran for autistic children at Labschool Umsida, Candi Sidoarjo and what are the obstacles and supports in the learning process. This study uses a qualitative research type. Using a Field Research approach or field research where information is obtained from research subjects through interviews, observations, and documentation as data collection instruments. The findings of this study indicate that in the process of learning the Koran for autistic children, they use audio murottal media and visual media using pictures, cards and blocks. The rest just listen and imitate because they still can't distinguish the shape of the hijaiyah letters. Moreover, the school still does not have its own clinic center that can identify student needs. Apart from that, all the apperceptions that the school has built for students and guardians of students are very helpful and supportive in the learning process so far as well as the facilities owned by the school which are so diverse and can meet the needs of autistic students in learning the Qur'an.